Pilar de Valderrama, The Guiomar of Antonio Machado. Ignored writer and outraged muse - Rubio Alvarez (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2018)
Pilar de Valderrama, belonging to the Generation of 27, has been one of the many writers forgotten by contemporary literary criticism. In this article we offer an updated biography of the poet and playwright who was also Antonio Machado's muse and we analyzed the personal attack she suffered especially since the 1970s, and the lack of scientific rigor of these criticisms.